Factors Responsible for Delay in Initiation of Insulin Treatment in Type-2 Diabetes Mellitus Patients with Secondary Failure of Oral Hypoglycemic Agents - Muhammad Mujeeb Khan , Shehzad Manzoor , Mohammad Ali Khalid , Maliha Gull Tarrar , Faiza Aslam , Syed Irfan Ahmed (Journal of Rawalpindi Medical College, 2018)
Background: To assess patients’ and physicians’ perceptions regarding factors responsible for delay of Insulin initiation and compared. Methods: In this cross sectional study using mixed quantitative and qualitative approach, quantitative component included structured interviews of 400 Type 2 Diabetic patients with failure to oral hypoglycemic agents (equally stratified based on gender and public or private health care settings) who had not initiated Insulin despite physicians advice. For qualitative aspect, 4 Focus group discussions with 29 consultant physicians of diabetic patients and four including 31 diabetic patients with delay were conducted. The factors responsible for delay and mean duration of delays were assessed and also compared based on gender and health care type. Results: The mean duration of diabetes in 400 patients was 12.91±3.78 years while the duration of delay in months was 23.08±14.62 months with highly statistically significant increase in female patients. Patients identified fear of injection or needle phobia as the commonest factor (24.62%), followed by fear of side effects of Insulin (18.87%). Consultant physicians in addition to same above factors also mentioned the role of quacks and fear of loss of patients by doctors as important factors. Conclusion: Factors identified by patients and physicians responsible for delay of initiation of insulin included perceptions of fears, difficult and lifelong application, cost, storage issues, last resort of treatment, misdirection from quacks and patients reluctance tempting doctors to hold up insulin till inevitable.